Shenyuan granules improve cellular senescence through Klotho-mediated p16/p21 signaling pathway in diabetic kidney disease - Guo, Xinyuan; Zhang, Siyang; Sun, Qingqing; Li, Huimeng; Wang, Lan (Frontiers in Medicine, 2025)
ContextShenyuan Granules (SYG), a traditional Chinese medicine preparation, are clinically used for treating chronic kidney diseases. However, the role of Klotho in modulating cellular senescence via the p16/p21 pathway and its involvement in the therapeutic effects of SYG in diabetic kidney disease (DKD) remains unclear.ObjectiveThis study investigated the regulatory effects of SYG on the Klotho gene and their mechanisms in alleviating cellular senescence in DKD.Materials and methodsUtilizing an adenine-induced DKD model in db/db mice and AGE-stimulated HK-2 cells, this research assessed renal tissue for cellular senescence and pathological changes. Techniques such as SA-β-Gal, HE, and PAS staining were employed to observe these changes. The study also measured the expression levels of senescence-associated and anti-aging markers including Klotho, cyclin-dependent kinase inhibitor 2A (p16), cyclin-dependent kinase inhibitor p21 (p21), plasminogen activator inhibitor-1. Quantification of senescent cells was performed using SA-β-Gal staining, while mRNA and protein expressions were analyzed using immunofluorescence, real-time PCR, and Western blotting.ResultsSYG treatment significantly improved renal function in db/db mice and alleviated histopathological lesions. SA-β-Gal staining demonstrated a marked decrease in senescent cell burden, while immunohistochemistry and Western blotting revealed downregulation of p16, p21, and PAI-1 and upregulation of Klotho expression (p < 0.05). In vitro, Klotho overexpression in AGE-stimulated HK-2 cells significantly suppressed senescence-associated markers and restored Lamin B1 expression. Similarly, treatment with SYG-containing serum effectively downregulated p16, p21, and PAI-1 while upregulating Klotho expression. These findings suggest that SYG attenuate renal cellular senescence by modulating the Klotho-mediated p16/p21 signaling pathway.DiscussionThis study highlights the potential of SYG to alleviate cellular senescence in DKD by targeting the Klotho-mediated p16/p21 pathway. These findings provide a foundation for developing senescence-focused therapies in chronic kidney disease management.